The Positive Relationships Between Paranoia, Perceptions of Workplace Bullying, and Intentions of Workplace Deviance in United Kingdom and French Teachers: Cross-Cultural Aspects - Lopes, Bárbara Cristina Da Silva; Bortolon, Catherine; Macioce, Válerie; Raffard, Stéphane (Frontiers in Psychiatry, 2020)
Cognitive models of psychopathology were applied to inform the relationships between paranoia, workplace bullying and deviance in UK and French teachers. Sixty-six UK teachers and fifty French teachers were asked to fill in an online survey comprised of the Green et al.’s Paranoia Thought Scales, Negative Acts Questionnaire, Depression, Anxiety and Stress scales and Workplace Deviance Scale. Mann-Whitney tests showed that UK teachers report significantly more perceptions of work-related bullying and intentions of workplace deviance than French teachers. Mediation analyses showed that paranoia impacted on intentions of workplace deviance but workplace bullying did not mediate this association in UK teachers. Paranoia showed an indirect effect on intentions of workplace deviance that was mediated by negative affect in French teachers. Culturally tailored psycho-social interventions should be implemented targeting teachers’ paranoid thinking and workplace bullying in order to deter teachers from engaging in workplace deviance and to promote their well-being.